On China's trade surplus - YUAN, Tao (SpringerBriefs in Business, 2014)
China's trade surplus is an essential question, but there are many popular misconceptions about it, a fact that prompted the creation of this book, On China's Trade Surplus. It will help readers to understand the manner in which China's foreign trade and China's role in global trade have developed, and to how to benefit from trade with China. In this book, many hot topics are analyzed, such as: What promotes China's trade surplus? Why doesn't it have a trade deficit? What are the relations between trade frictions and China's trade surplus, and how can trade frictions be reduced? What is the deeper meaning of the U.S. trade deficit with China?